Using Response Surface Methodology for Economic and Environmental Trade-offs at the Farm Level - James C. Ascough; Eihab M. Fathelrahman; Dana L. Hoag (Air, Soil and Water Research, 2013)
United States farmers typically spend over $10 billion annually on commercial fertilizer. Chemical inputs such as nitrogen (N) are essential for maintaining crop yields; however, farmers often apply excessive N inputs as an insurance policy. Nitrogen fertilizer consumption in the U.S. quadrupled from 3 million metric tons in 1961 to over 12 million metric tons in 2004, and per ha N fertilizer use quadrupled. Increase in N use has been associated with the impairment of U.S. streams, lakes, and aquifers. The objective of this research study was to develop an integrated farm-level economic/environmental risk framework for trade-off analysis between farm profitability and environmental externalities (impacts). Results indicated that there was no single point of optimal trade-off between farm profitability and the environment. Additionally, trade-offs between farm profit and environmental impacts varied significantly depending on the choice of cropping or tillage system.